Upaya Meningkatkan Minat dan Hasil Belajar melalui Model NHT pada Pembelajaran PKn Kelas IV SD Muhammadiyah Kebumen Tahun Pelajaran 2020/2021 - Anjar Fita Lestari; Suyoto Suyoto; Arum Ratnaningsih (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Civics learning which is still rare using the NHT model makes students' interest and learning outcomes of Civics low. This study aims to increase: (1) students' interest in learning Civics by using the NHT model in SD Muhammadiyah Kebumen and (2) student learning outcomes in Civics by using the NHT model at SD Muhammadiyah Kebumen. This type of research is classroom action research which is carried out in two cycles. The subjects in this study were fourth grade students of SD Muhammadiyah Kebumen, totaling 14 students. Data collection techniques using observation, questionnaires, tests and documentation. Data analysis used quantitative and qualitative descriptive. The success indicator used in student learning interest can be said to be successful if it has passed the 80% percentage, for student learning outcomes with a value of 70 and classical completeness of 70%. The results of this study can increase the interest and learning outcomes of fourth grade students of SD Muhammadiyah Kebumen. Judging from the results of observations, the average student interest in Civics learning has increased from the first cycle of 62.14% to 82.14% in the second cycle and is in the very good category. Judging from the results of the questionnaire, the average student interest in Civics learning has increased from the first cycle of 65.42% to 81.28% and is in the very good category. In line with that, the average student learning outcomes increased, namely from pre-cycle of 40 with less category increased to 65.71 with sufficient category in the first cycle, and in the second cycle increased again to 82.14 with good category.